Sub/Super Solutions Methods for a Class of Fractional Laplacian Systems - Guefaifia, Rafik; Rasouli, Sayyed Hashem; zennir, Khaled (Discontinuity, Nonlinearity, and Complexity, 2026)
One of the most commonly used methods for elliptic models is the method of analysis of Sub/super solutions. A fractional powers of the Laplace operator is considered. By using sub-super solutions method, we show the existence of weak positive solution for class of elliptic systems in bounded domains. Our results are natural extensions from the previous recent papers.